Resilience Reflected In Suzanne Collin's The Hunger Games Novel (2008): An Individual Psychological Approach - Nugroho, Wisnu Catur; , Dr. Phil. Dewi Candraningrum, S.Pd, M.Ed; , Drs. Abdillah Nugroho, M.Hum (2013)
The object of this research is the novel entitled The Hunger Games, by Suzanne Collins. The major problem of this study is to investigate how the resilience to stay alive reflected in Suzanne Collins's The Hunger Games novel specifically viewed from individual psychological approach. In conducting this study, the researcher uses qualitative research whose data are based on primary data source that is the novel Suzanne Collins's The Hunger Games itself, and secondary data sources is references and materials related to the study picking up from the books or internet, and other data which deal with the research. Both data are collected by conducting library research and analyzed by descriptive analysis. The results of this study are as follows: based on the structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, theme is supporting each other to produce a good quality novel. Then, based on the individual psychology analysis, the study shows that the problem faced by the major character is her own psychology condition to decide the appropriate ways for her life. This novel also shows the process how the resilience to stay alive will produce the amazing result.